GENETIC POLYMORPHISMS OF MTHFR (677T AND 1298C) AND HOMOCYSTEINE METABOLISM AS MATERNAL RISK FACTOR FOR DOWN 'S SYNDROME PATIENTS IN NORTH INDIAN POPULATION. - SANJEEV KUMAR PANDEY; PANKAJ KUMAR MOHANTY; SUNIL KUMAR POLIPALLI; SEEMA KAPOOR (International Journal of Pharma and Bio Sciences, 2013)
Background &Aim: Down syndrome (DS) is caused by the presence of three copies of chromosome 21, in most cases due to the failure of chromosomal segregation during maternal meiosis (meiotic nondisjunction). Despite substantial research, the molecular mechanism underlying non-disjunction of trisomy 21 are poorly understood, as there was scanty data available from India the study was designed to investigate the MTHFR C677T and A1298C polymorphisms, with homocysteine as a maternal risk factor for DS. Materials and Methods: Eighty mothers of individuals with confirmed full trisomy 21, and 100 control mothers of the north Indian population were evaluated. Molecular analysis of MTHFR C677T and A1298C polymorphisms was performed by PCR-RFLP method. Biochemical correlation of total serum homocysteine was evaluated. Results: The frequency of genotypes of MTHFR were 677CC (82.6%), 677CT (15.4%) and 677TT (2.0%) in the patients with Down’s syndrome, and among the 100 individuals of the control group, genotypes 677CC (92.2%), 677 CT (6.12%) and 677TT (1.6%) were found. As for polymorphism 1298C, the patients with Down’s syndrome presented genotypes with frequencies 1298AA (15.0%), 1298AC (52.5%) and 1298CC (32.5%) respectively and in the control group the frequencies of genotypes were 1298AA (60.0%), 1298AC (22.0%) and 1298CC (17.0%) respectively. Homocysteine concentrations were significantly different in women with an MTHFR 1298CC genotype according to the group (case or control), being higher in DS mothers than in control mothers. Conclusion: No correlation was observed in MTHFR gene polymorphism 677T in DS. However, the MTHFR gene polymorphism at position 1298, mainly genotype 1298CC that reduces the enzyme efficiency, was more frequent in the group of Down’s Syndrome patients, suggesting its involvement in mechanisms related to chromosomal imbalances.